Liver Involvement in Langerhans Cell Histiocytosis A case report (Northern International Medical College Journal, 2016)
Langerhanscell histiocytosis (LCH) (Histiocytosis X) is a rare disease of unknown cause characterized by oligoclonal proliferation of Langerhans cells. It occurs mostly in children and young adults and involves one or more body systems such as bone, hypothalamus, posterior pituitary gland, lymph nodes, liver or various soft tissues. The diagnosis is always made by a histological approach. A 3.5-year old male child with LCH involving multiple systems, including the skin, lungs, liver with clinical signs of diabetes insipidus. The patient was diagnosed following a skin biopsy that revealed infiltration of Langerhans cells. This case report would increase the awareness of pediatricians about the multisystem involvement in LCH.Northern International Medical College Journal Vol.7(2) Jan 2016: 158-160